High Fe-Loading Single-Atom Catalyst Boosts ROS Production by Density Effect for Efficient Antibacterial Therapy - Chen, Si; Huang, Fang; Mao, Lijie; Zhang, Zhimin; Lin, Han; Yan, Qixin; Lu, Xiangyu; Shi, Jianlin (Nano-Micro Letters, 2024)
The current single-atom catalysts (SACs) for medicine still suffer from the limited active site density. Here, we develop a synthetic method capable of increasing both the metal loading and mass-specific activity of SACs by exchanging zinc with iron. The constructed iron SACs (h3-FNC) with a high metal loading of 6.27 wt% and an optimized adjacent Fe distance of 4 Å exhibit excellent oxidase-like catalytic performance without significant activity decay after being stored for six months and promising antibacterial effects. Attractively, a “density effect” has been found at a high-enough metal doping amount, at which individual active sites become close enough to interact with each other and alter the electronic structure, resulting in significantly boosted intrinsic activity of single-atomic iron sites in h3-FNCs by 2.3 times compared to low- and medium-loading SACs. Consequently, the overall catalytic activity of h3-FNC is highly improved, with mass activity and metal mass-specific activity that are, respectively, 66 and 315 times higher than those of commercial Pt/C. In addition, h3-FNCs demonstrate efficiently enhanced capability in catalyzing oxygen reduction into superoxide anion (O2·−) and glutathione (GSH) depletion. Both in vitro and in vivo assays demonstrate the superior antibacterial efficacy of h3-FNCs in promoting wound healing. This work presents an intriguing activity-enhancement effect in catalysts and exhibits impressive therapeutic efficacy in combating bacterial infections. Highlights: 1 Fe single-atom catalysts (h3-FNCs) with high loading, high catalytic activity and high stability were synthesized via a method capable of increasing both the metal loading and mass-specific activity by exchanging zinc with iron. 2 The “density effect,” derived from the sufficiently high density of active sites, has been discovered for the first time, leading to a significant alteration in the intrinsic activity of single-atom metal sites. 3 The superior oxidase-like catalytic performance of h3-FNCs ensures highly effective bacterial eradication.